THE INFLUENCE OF STORE ATMOSPHERE AND SOCIAL MEDIA MARKETING ON IMPULSE BUYING BEHAVIOR - Rohmad Prio Santoso; Rahmad Risan (Media Inovasi Pendidikan dan Publikasi, 2023)
This research aims to determine the influence of store atmosphere and social media marketing on impulse buying behavior. The research method used in this research is a quantitative research method with a sample size of 30 respondents. The data collection technique uses a questionnaire and the data analysis technique uses the classic assumption test and multiple linear regression test with hypothesis testing using the t test and F test. The findings in this research state that the Store Atmosphere variable has a significant effect on Impulse Buying behavior by 53.2% and the second stated that the social media marketing variable had a significant influence on Impulse Buying by 40.3%. Store Atmosphere and social media marketing simultaneously influence Impulse Buying with a calculated F value of 86.13%. In this way, it can be concluded that the three hypotheses developed in this research have been proven.